Analisis Komunikasi Kreatif Bank Mandiri Melalui Pemanfaatan Media Sosial Youtube Pada Iklan “Jadi Lebih Baik” - Hana, Aulia Fadhilah; Desrizal; Dewi, Arie; Wulandari, Siti Hardiati (CV ODIS, 2024)
Advertising is an important aspect in the business world to attract attention and reach the target audience. The important thing to do in the process of creating a successful advertisement is to do creative communication. This research aims to explore the utilization of creative communication in the advertising process by Bank Mandiri. Through a qualitative descriptive study, this research analyzes the creative communication strategies used in Bank Mandiri's “Jadi Lebih Baik